Communication-High-Performance and Non-Precious Bifunctional Oxygen Electrocatalysis with Binuclear Ball-Type Phthalocyanine Based Complexes for Zinc-Air Batteries - ÖZKAYA, ALİ RIZA; ÖZER, METİN (ELECTROCHEMICAL SOC INC, 2016)
In this study, the electrocatalytic activities and zinc-air battery performances of newly synthesized 4,4'-{(diphenylmethylene) bis(4,1-phenylene)bis(oxy)}-bridged binuclear ball-type iron(II), cobalt(II) and zinc(II) phthalocyanine, M2Pc2 complexes were investigated. Electrochemical measurements indicated that Fe2Pc2 complex is a good alternate to Pt/C catalyst. (C) 2016 The Electrochemical Society. All rights reserved.
Keywords: IRON PHTHALOCYANINE; REDUCTION